Indonesian Language Learning Approach in the Merdeka Curriculum: A Literature Study on Implementation and Effectivenes - Loso Judijanto; Amar Salahuddin; Erna Yantiningsih; Linda Handayani; M. Imelda Kusumastuty (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to examine the implementation and effectiveness of the Indonesian language learning approach in the Merdeka Curriculum through a literature review. The research conducted in this study uses a library research or literature study approach. The researcher relies on various literatures to obtain research data, with a qualitative approach that results in data in the form of words or descriptions. Based on the literature review conducted, the Indonesian language learning approach in the Merdeka Curriculum has great potential to improve the quality of education by providing space for more flexible and contextual learning tailored to students' needs. However, its implementation faces significant challenges, particularly related to teachers' readiness, infrastructure limitations, and a still-limited understanding of the fundamental principles of this curriculum. The success of the Merdeka Curriculum in Indonesian language learning largely depends on sustained support from various parties, such as the government, which must provide adequate training and infrastructure, as well as the involvement of the community and parents in the educational process. With good collaboration, this curriculum can improve the overall quality of education and have a positive impact on the younger generation of Indonesia.